The importance of service quality for competitive advantage – with special reference to industrial product - Dominic P, Dhanapal Durai; Goh , Kim Nee; Wong, Diana; Chen, Yoke Yie (2010)
Current competitive environment induced by globalisation and advances in information technology have forced companies to focus on managing customer relationships, and in particular customer satisfaction and customer loyalty in order to efficiently maximise revenues. In the age of customer delivering quality service, it is considered an essential strategy for success and survival in today’s competitive environment. The focus of any supply chain management system is to provide all customers with the level of service they require and as no budget is unlimited, there is need to prioritise services. The purpose of the paper is to examine and develop a better understanding of relationship between service quality (SQ), customer relationship management (CRM), customer satisfaction (CS) and customer loyalty (CL) which might lead to companies’ competitiveness advantage. Methodology of critical value analysis is used for setting customer service priorities and an analytical hierarchy process approach is used for evaluation of importance of customers. This paper concludes by discussing the survey findings and proposing future research.